1992
DOI: 10.1042/bj2820007
|View full text |Cite
|
Sign up to set email alerts
|

Use of annexin-V to demonstrate the role of phosphatidylserine exposure in the maintenance of haemostatic balance by endothelial cells

Abstract: Annexin-V (PAP-I, lipocortin-V) acts as a potent anticoagulant in vitro by binding to negatively charged phospholipids with higher affinity than vitamin K-dependent proteins, with a Kd in the 10(-10) M range. The purpose of the present study was to use annexin-V as a probe to assess the catalytic potential of phospholipids in pro- and anti-coagulant reactions in purified systems and at the surface of endothelial cells in culture after stimulation. Procoagulant tissue factor and anticoagulant thrombomodulin act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 55 publications
(60 reference statements)
3
50
3
Order By: Relevance
“…4A). The saturating inhibitory concentration of annexin V on phospholipid-dependent processes has previously been shown to be dependent on phospholipid concentration (24). With 0.13 j,g of apoptotic cells per ,ul, half-maximal reversal of the procoagulant effect was observed at 150 ,tM annexin V (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…4A). The saturating inhibitory concentration of annexin V on phospholipid-dependent processes has previously been shown to be dependent on phospholipid concentration (24). With 0.13 j,g of apoptotic cells per ,ul, half-maximal reversal of the procoagulant effect was observed at 150 ,tM annexin V (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…1). Endothelial PS exposure supports the assembly of coagulation complexes on the cell surface, leading to thrombin generation 31,32 . Consistent with this, staining of the endothelium with an anti-fibrin monoclonal antibody revealed localized fibrin generation at the sites of needle injury, confirming a-thrombin generation (Fig.…”
Section: Procoagulant Endothelial Cells Recruit Platelets and Leukocymentioning
confidence: 99%
“…This supposition is contradicted by a number of studies, including those showing that endothelial cells, which are not considered procoagulant, nonetheless express significant levels of phosphatidylserine on their surface. 23 This phosphatidylserine is important for maintaining the anticoagulant activity of endothelium by enhancing thrombomodulin activity. 23 A direct comparison of platelets and phospholipids has shown that platelets have complex coagulant activities that are not completely mimicked by phospholipids.…”
Section: Cascade Model Of Coagulationmentioning
confidence: 99%